Pelatihan Life Skill Bagi Mahasiswa Terdampak Covid-19 di Kota Serang - Eka Julaiha; Qodir, Abdul; Jihan Nur Azizah; Alwi Haqiqi (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The Covid-19 pandemic has affected various aspects of human life throughout the world. Since its appearance in early 2020, this virus has caused some people in the world to experience shock and disruption in various aspects of life. Apart from that, the impact of this pandemic has also greatly influenced the educational aspect where almost all countries require the teaching and learning process to be carried out online or online. This condition is very worrying and makes it possible for economically disadvantaged students to think about it Drop out from campus due to economic problems. Meanwhile, it is difficult for them to meet their daily needs, plus the internet quota costs are not cheap to participate in all the online learning activities required by the campus. Therefore, we are trying to create a service program entitled Training Life Skills for Students Affected by COVID-19 in Serang City. Development implementation methods life skills This method uses Education for Sustainable Development (EfSD). The stages of training activities provided to students affected by COVID-19 in the city start with field observations, program outreach, training & workshops, to visits carried out by students. Based on the results of this service, students in the city of Serang can make optimal use of life skills training and can carry out follow-up plans and readiness for continued assistance. So life skills (life skills) can be formed well. Keywords; COVID-19, EFSD, Life Skills, Pandemic